2014
DOI: 10.1016/j.vph.2013.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Decline in platelet count and long-term post-PCI ischemic events: Implication of the intra-aortic balloon pump

Abstract: In this patient population the use of IABP, but not thrombocytopenia per se, is a possible primary cause of worse ischemic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…It is interesting that, in some cases, thrombocytopenia may also indicate increased risk of ischemic events, which seems to be a paradox to our results4950. However, further studies found that, in the population of ischemic patients, it was the use of intra-aortic balloon pump (IABP), but not thrombocytopenia per se, serves as a possible primary cause of adverse ischemic events4950.…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…It is interesting that, in some cases, thrombocytopenia may also indicate increased risk of ischemic events, which seems to be a paradox to our results4950. However, further studies found that, in the population of ischemic patients, it was the use of intra-aortic balloon pump (IABP), but not thrombocytopenia per se, serves as a possible primary cause of adverse ischemic events4950.…”
Section: Discussioncontrasting
confidence: 54%
“…However, further studies found that, in the population of ischemic patients, it was the use of intra-aortic balloon pump (IABP), but not thrombocytopenia per se, serves as a possible primary cause of adverse ischemic events4950. It reminds us that when we use PLR to predict the prognosis of ACS, we should make our judgment according to each specific matter considering possible confounding factors.…”
Section: Discussionmentioning
confidence: 99%
“…Previous researches 41 42 showed thrombocytopenia (TC) is associated with increased risk of bleeding and ischemic events. Studies also showed that intra-aortic balloon pump (IABP) was a cause of both TC 43 and PPA 40 and influenced the long-term ischemic events. Although the significant difference in mortality between patients with and without baseline TC was not found in our study, the change of platelet count following IABP should be taken into account in the process of DAPT.…”
Section: Discussionmentioning
confidence: 99%
“…Longer CPB duration and the use of IABP have been associated with an increased risk of thrombocytopenia. Studies have reported varying degrees of PLT dysfunction and reduction associated with IABP use ( 22 , 23 ). These effects may be influenced by factors such as PLT activation, shear stress, PLT adhesion to the IABP surface, and altered blood flow dynamics ( 24 ).…”
Section: Discussionmentioning
confidence: 99%